The relationship between humidity, light and the activity pattern of a velvet worm, Epiperipatus sp. (Onychophora: Peripatidae), from Bahía Drake, South Pacific of Costa Rica - Barquero González, José Pablo (2018)
Even though the Onychophora represent a whole phylum, observations of their activity pattern in nature are almost non-existent. Here we report on the relationship between humidity and light and activity pattern of a new species of velvet worm, genus Epiperipatus, from four years of field observations in the South Pacific of Costa Rica. We found that most activity occurs during the driest and darkest nights of the year, in contrast with theoretical predictions.